Recombinant RGD-disintegrin DisBa-01 blocks integrin αvβ3 and impairs VEGF signaling in endothelial cells - Taís M. Danilucci; Patty K. Santos; Bianca C. Pachane; Graziéle F. D. Pisani; Rafael L. B. Lino; Bruna C. Casali; Wanessa F. Altei; Heloisa S. Selistre-de-Araujo (Cell Communication and Signaling, 2019)
Abstract Background Integrins mediate cell adhesion, migration, and survival by connecting the intracellular machinery with the surrounding extracellular matrix. Previous studies demonstrated the interaction between αvβ3 integrin and VEGF type 2 receptor (VEGFR2) in VEGF-induced angiogenesis. DisBa-01, a recombinant His-tag fusion, RGD-disintegrin from Bothrops alternatus snake venom, binds to αvβ3 integrin with nanomolar affinity blocking cell adhesion to the extracellular matrix. Here we present in vitro evidence of a direct interference of DisBa-01 with αvβ3/VEGFR2 cross-talk and its downstream pathways. Methods Human umbilical vein (HUVECs) were cultured in plates coated with fibronectin (FN) or vitronectin (VN) and tested for migration, invasion and proliferation assays in the presence of VEGF, DisBa-01 (1000 nM) or VEGF and DisBa-01 simultaneously. Phosphorylation of αvβ3/VEGFR2 receptors and the activation of intracellular signaling pathways were analyzed by western blotting. Morphological alterations were observed and quantified by fluorescence confocal microscopy. Results DisBa-01 treatment of endothelial cells inhibited critical steps of VEGF-mediated angiogenesis such as migration, invasion and tubulogenesis. The blockage of αvβ3/VEGFR2 cross-talk by this disintegrin decreases protein expression and phosphorylation of VEGFR2 and β3 integrin subunit, regulates FAK/SrC/Paxillin downstream signals, and inhibits ERK1/2 and PI3K pathways. These events result in actin re-organization and inhibition of HUVEC migration and adhesion. Labelled-DisBa-01 colocalizes with αvβ3 integrin and VEGFR2 in treated cells. Conclusions Disintegrin inhibition of αvβ3 integrin blocks VEGFR2 signalling, even in the presence of VEGF, which impairs the angiogenic mechanism. These results improve our understanding concerning the mechanisms of pharmacological inhibition of angiogenesis.